2017
DOI: 10.1007/s11149-017-9338-6
|View full text |Cite
|
Sign up to set email alerts
|

Weakening political connections by means of regulatory reform: Evidence from contracting out water services in Spain

Abstract: One area of public policy where rent-seeking and favoritism is relatively common is the contracting out of public services. Private firms can improve their chances of obtaining contracts by bribing politicians or public servants and funding political parties. In the same vein, firms can gain access to policymakers by hiring influential former politicians -a practice commonly referred to as revolving-doors. In this paper, we use information from 922 privatizations of water services in Spanish municipalities bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…For example, within the Anglo-Saxon model, the US has a number of laws (Clayton Act, Sherman Act) that, for example, provide severe anti-trust laws and declare interlocks among competing firms illegal, whereas the continental model leads to banks influencing corporate affairs [108]. To date, there are very few studies conducted in Spain, and they are focused on the link between political connections and compensation policies in saving banks, the informativeness of accounting earnings [38], as well as on the study of hiring influential former politicians in the revolving doors [39]. In turn, there are no studies on the relationship between interlocks, former politicians, regulations, and acquisitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, within the Anglo-Saxon model, the US has a number of laws (Clayton Act, Sherman Act) that, for example, provide severe anti-trust laws and declare interlocks among competing firms illegal, whereas the continental model leads to banks influencing corporate affairs [108]. To date, there are very few studies conducted in Spain, and they are focused on the link between political connections and compensation policies in saving banks, the informativeness of accounting earnings [38], as well as on the study of hiring influential former politicians in the revolving doors [39]. In turn, there are no studies on the relationship between interlocks, former politicians, regulations, and acquisitions.…”
Section: Discussionmentioning
confidence: 99%
“…This fact may have influenced the interpretation of the results in previous studies because of the existing legal, judicial, and cultural differences across countries [34][35][36][37]. The very few studies that have been conducted in Spain have focused on the relationship between political connections and compensation policies in saving banks, the informativeness of accounting earnings [38], and the importance of hiring influential former politicians in the revolving doors [39].…”
Section: Introductionmentioning
confidence: 99%
“…First, several concentration indices for the period 1995-2019 are calculated, comprising two symmetric 12-year subperiods before and after the legal reform of procurement passed in Spain in 2007 (Law 30/2007 on Public Sector Contracts). That reform, together with the parallel reform of the legal framework for donations to political parties (Law 8/2007 on the Financing of Political Parties) reduced politically driven favoritism in the adjudication of water contracts in Spain (Albalate et al 2017). Merging the information provided in Albalate et al (2017) on Spanish municipalities with private delivery of urban water services and the database specifically produced for this article, a greatly enlarged database of municipalities is compiled, which includes up to 988 municipalities (in 2019) with a private provider of urban water services for which the name is known; this sample covers over 50 percent of the private water market in Spain in terms of municipalities, and 70 percent in terms of population.…”
Section: Discussionmentioning
confidence: 99%
“…Coviello, Guglielmo, and Spagnolo (2018) found that more discretion in the procurement process is positively related to the probability of incumbents winning the new contract, and that incumbent renewal can actually improve performance. 1 In Spain, a recent article by Albalate et al (2017) confirmed that the passing of Law 30/2007 on Public Sector Contracts-which improved transparency in public procurement, regarding both publicity and non-discretionary decisionssubstantially weakened the connections between political parties and big players in the water industry when it came to the contracting-out of urban water services. Hence, the third hypothesis is: Hypothesis 3: Greater transparency in awarding public contracts increases the probability of alternation.…”
Section: Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation